Hypothermia detection in low birth weight neonates using a novel bracelet device. (18th August 2019) - Tanigasalam, Vasanthan; Vishnu Bhat, B.; Adhisivam, B.; Balachander, Bharathi; Kumar, Harichandra
Abstract: Objective: The objective of this study is to assess the diagnostic accuracy of a novel hypothermia monitoring and alert bracelet device (BEMPU Bracelet) in low birth weight (LBW) neonates weighing less than 2000 g. Design: This was a controlled prospective study. Setting: This study was done in the step-down nursery of a tertiary level newborn unit of a major teaching hospital in India. Methods: Eligible cases fulfilling inclusion criteria were given BEMPU Bracelets for a period of 24 h. A comparison was made between skin temperatures taken at the axilla by a mercury thermometer and skin temperatures taken at the wrist by the BEMPU Bracelet. Temperatures were taken every 6 h and every time the BEMPU Bracelet alarmed. Trained nurses obtained temperature measurements on newborns during their 24-h stay in the hospital step-down nursery. Results: A total of 461 neonates were screened for hypothermia, giving 2428 temperature readings. Three hundred and eleven of 461 babies experienced hypothermia at some point. The 461 babies studied experienced 495 episodes of hypothermia in total. The sensitivity and the specificity of the bracelet in diagnosing hypothermia were 98.6% and 95% respectively. The positive and negative predictive values of the bracelet were 83.6% and 99.6%, respectively. The accuracy of the bracelet in diagnosing hypothermia was 95.8%. Conclusion: The BEMPU Bracelet is an accurate screening tool to detect and alert for neonatal hypothermia, thereby facilitating prompt management, which could prevent complications.